2003
DOI: 10.1007/s00467-003-1154-9
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of childhood nephrotic syndrome in Indian children

Abstract: Nephrotic syndrome in children is a clinical manifestation of different histopathological subtypes. There is a paucity of recent large studies dealing with the histopathological spectrum from developing countries. A prospective study was performed from January 1990 to December 2000 at our center, involving 600 children (with age of onset up to 16 years) with idiopathic nephrotic syndrome (INS). The objectives were: (1) to study the histopathological distribution of different subtypes of INS and (2) to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 18 publications
14
39
0
Order By: Relevance
“…FSGS was the second most common cause. This is in accordance with observations made by others29 and some reported it as the most common cause in children above 8 years of age 30. The incidence of primary and secondary glomerular diseases is similar to that found in a study conducted in Iraq 18…”
Section: Discussionsupporting
confidence: 93%
“…FSGS was the second most common cause. This is in accordance with observations made by others29 and some reported it as the most common cause in children above 8 years of age 30. The incidence of primary and secondary glomerular diseases is similar to that found in a study conducted in Iraq 18…”
Section: Discussionsupporting
confidence: 93%
“…In interpreting and comparing histologic reports from different centres, the indications for renal biopsy, steroid exposure, the time periods of the study which have been shown to produce varying results over decades in the same location [20, 26, 35] need to be critically considered. Other important considerations are patient population in terms of age [36–38], race and whether native or transplant kidneys are studied. All the patients studied were black Nigerians and the kidneys were all native kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate biopsy specimen was defined as presence of at least five glomeruli in the specimen on LM, similar to previously published studies. 4,5 Nephrotic syndrome was defined as oedema, proteinuria >40 mg/m 2 per h on timed sample and hypoalbuminaemia <2.5 g/dL. ANS was defined as haematuria, oliguria, oedema, hypertension (≥95th centile for age) and GFR < 75 mL/min per 1.73 m 2 by Schwartz's formula.…”
Section: Methodsmentioning
confidence: 99%